Research estimates of the influence factors on the arcs lengths system regulation modes of an electric arc furnace with regulator ARDM-T - Paranchuk, Ya. S.; Holovach, I. R.; Matsyhin, A. B.; Tsiapa, V. B. (Visnyk of Vinnytsia Politechnical Institute, 2014)
The estimates of the influence factors on the arcs lengths system regulation modes of an electric arc furnace with regulator ARDM-T by using regression and correlation analysis are shown. The results of research have been obtained.